LOW-INCOME FAMILIES ARE UNHEALTHY DUE TO THE PROCESSED FOODS THEY BUY - M SURESH,; SRI, J USHA; GIRIJA, Dr. MAMIDI; KUMAR, CH VIJAY (The journal of contemporary issues in business and government, 2019)
In the United States, many low-income families are unable to afford nutritious foodstuffs. Families in the medium to upper income range are more likely to buy healthful food. For the goal of this study, I want to examine how low-income families' poor health is caused by their preference for processed food over more nutritious options. Low-income families are unhealthy because they rely on inexpensive, pre- made foods that are heavy in salt, which raises blood pressure and increases the risk of heart disease. In the second part, we'll talk about where and what low- income families are most likely to turn to for low- cost meals. If there are any possibilities for low- income families who want to eat healthfully, we'll talk about them in the third section. Programs that collect food contributions from the public and use coupons for discounts, as well as food stamps, are the most probable candidates. The pricing of healthy,non-processed food items will be discussed in the fourth aspect. The shortage of nutritious food and the high demand for it among the general population are two such issues. The fifth part of this section will focus on the harmful impacts of a lack of access to good meals on children in low-income homes. Children's health risks and poor eating habits may both be harmed as a result of this practise. Low- income households are more at risk of developing health problems because of the factors listed above.